MONITORING PRODUKSI TELUR AYAM DENGAN SMART SYSTEM BERBASIS INTERNET OF THINGS - Ariadi, Fadly; Andrian, Tio; Budi Prasetyo, Agus (PT Triputra Sejahtera Prima, 2024)
One of the food needs with quite high interest is eggs, more specifically chicken eggs. Chicken eggs are one of the food needs that are sought after by many people as evidenced by data issued by BPS or the Central Statistics Agency. Based on data from the Central Statistics Agency (BPS), the average -The average consumption of chicken eggs in Indonesia in 2022 will be 2,336 kilograms (kg) per capita per week. If viewed from a benefits perspective, the benefits of chicken eggs are that they provide highly nutritious food substances, but not only that, they are also relatively cheap compared to other animal products, which means that demand for chicken eggs will tend to continue to increase. However, chicken egg farmers in several areas still experience difficulties in controlling production and monitoring chicken eggs because they still use extensive or traditional counting systems. This research was carried out with the aim of creating a chicken egg counting system that is integrated with an Android application where the egg production produced can be monitored or monitored directly via a mobile device. The methodology for efficient development of this project is proposed using ESP8266 which is connected to several sensors as a supporting monitoring tool and integrated with WiFi to send data directly. The result of this research is an egg production counting system that is connected to a gadget with an Android platform based on the Internet of things where production results can be monitored directly by every client who has access.